Who moved my holiday? Exploring the economic impact of the public holiday calendar on the hospitality sector - Paolo Figini; Veronica Leoni; Daniel C Quan (Tourism Economics, 2026)
This paper examines if and how the holiday calendar structure affects the hospitality sector’s performance. Countries typically adopt either fixed-date holidays (e.g., December 25), which can occasionally align or “bridge” with weekends, or fixed-day-of-week holidays (e.g., the month’s first Monday), which limit such extensions to 3-day weekends. We develop a theoretical extension of the standard labor–leisure model and empirically investigate its implications using 20 years of daily hotel data from Italy, a country characterized by fixed-date public holidays. Specifically, we assess hotels’ weekly performance according to the weekday on which a public holiday falls. Results show gains when public holidays plug-in, boosting short breaks, but do not support the existence of a specific “holiday bridging” effect, thus revealing that the overall economic impact of the weekday on which the holiday falls appears negligible. Findings inform policy debates on holiday scheduling and offer guidance for countries with different holiday systems.